Pengaruh Kualitas Pelayanan, Citra Merek, Komitmen terhadap Loyalitas Pelanggan Hotel Duta Palembang - Terinda, Jenika Pasya; Retno Budi Lestari (IPM2KPE, 2025)
This study aims to analyze the influence of service quality, brand image, and commitment on customer loyalty at Hotel Duta Palembang. The research employs a descriptive quantitative approach with a non-probability sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression tests. The results indicate that service quality, brand image, and commitment have a positive and significant impact on customer loyalty, both partially and simultaneously. The Adjusted R Square value of 65.8% shows that these three variables contribute significantly to customer loyalty. Hotel Duta Palembang is advised to enhance its technology-based complaint system, strengthen its brand image through unique experiences, and maintain a strong commitment to customers. This research can serve as a reference for future studies in developing strategies to improve customer loyalty in the hospitality industry. Keyword: Service Quality, Brand Image, Commitment, and Customer Loyalty